Når skurke digter helte hos Kierkegaard - Kaarsgaard, Stine Zink (Slagmark - Tidsskrift for idéhistorie, 2018)
The article is divided into three main sections. The article first considers the question of heroes and villains in Kierkegaard’s authorship broadly speaking. It then outlines the different roles of ‘the tragic hero’ which exposes the most explicit and repeated use of the word hero in Kierkegaard’s works. Finally it turns to the poet and reflects upon the double role of the poet as perhaps the closest we can get to a “villainish hero” in Kierkegaard’s authorship. ‘Heroes and villains’ is not something that is much discussed in Kierkegaard literature, and this fact foreshadows what may be an immediate suspicion; that there are none such as such in Kierkegaard’s works because the mere making of a hero (in language and image) always somehow withdraws the possibility of the hero from his or her own story. The only true hero in that sense may be the poet, because he makes life comprehensible, and yet as such he is also the only true villain, because he breaches between life and faith, making both appear but none for real.